CAMACHO PADILLA, Fernando, ESCRIBANO MARTÍN, Fernando, FARZAMNIA HAJARDOVOM, Nadereh y NEILA HERNÁNDEZ, José Luis (coords.) Miradas de Irán. Historia y cultura. Madrid, Catarata, 2021, 284 páginas. : Reseña por Samuel Jimeno Martín - JIMENO MARTÍN, Samuel (Al-Andalus Magreb, 2021)
Reseña